Protective role of N-trans-feruloyltyramine against β-amyloid peptide-induced neurotoxicity in rat cultured cortical neurons - Wipawan Thangnipon (2018)
Enhanced oxidative stress and inflammation play important roles in the pathogenesis of Alzheimer's disease (AD). Amyloid β-peptide (Aβ), a major component of amyloid plaques, is considered to have a causal role in the development and progress of AD by being the initiator of a pathological cascade leading to oxidative stress. The present study investigated the effect of N-trans-feruloyltyramine (NTF) purified from Polyalthia suberosa, an alkaloid shown to protect against oxidative stress and cell death. Pre-treatment of rat primary cortical cell cultures with 25-250μM NTF significantly attenuated 10μM Aβ 1-42 -induced neuronal death in a dose-dependent manner. Apoptotic cell death was demonstrated morphologically as well as by detection of the presence of activated caspase-3 and Bax, levels of which could be reduced by NTF pre-treatment. NTF also reduced production of reactive oxygen species induced by Aβ 1-42 . These findings suggest that the protective effect of NTF against Aβ 1-42 -induced neuronal death might be due to its antioxidative property. © 2012 Elsevier Ireland Ltd.